Experimental study on durability of fiber reinforced concrete: Effect of cellulose fiber, polyvinyl alcohol fiber and polyolefin fiber. (1st November 2021) - Xu, Haiyan; Wang, Zhijie; Shao, Zimeng; Cai, Libin; Jin, Hesong; Zhang, Zengzhao; Qiu, Zhihong; Rui, Xiaohao; Chen, Tiewei
Highlights: Concrete reinforced with cellulose fiber, polyvinyl alcohol fiber or polyolefin fiber of different dosages has different durability performance. Hybrid fiber is found to have a positive synergistic effect on concrete durability. Hybrid fiber combination of 1.2 kg/m 3 cellulose fiber, 2.0 kg/m 3 polyvinyl alcohol fiber and 2.0 kg/m 3 polyolefin fiber may achieve optimal synergistic effect on durability. Hybrid combinations can prolong service life of concrete in carbonization and chloride ion corrosive environment. Abstract: The durability of concrete reinforced by cellulose fiber (CTF), polyvinyl alcohol fiber (PF) and polyolefin fiber (VS) is comprehensively studied in this paper. Relevant durability tests are conducted to explore the effect of different fiber types and dosages on durability performance demonstrated in the resistance to drying shrinkage, water permeability, crack, carbonization and chloride ion penetration. Besides single fiber reinforced concrete, synergistic effect of hybrid fibers on durability is also studied, and the service life of fiber reinforced concrete in carbonization environment and chloride ion corrosive environment is further predicted. In addition, the structure of fiber reinforced concrete is analyzed from the micro perspective by using the optical and electron microscope. The results showed that: (1) The addition of CTF can effectively enhance the all five aspects of durability performance, including the resistance to drying shrinkage, water permeability, crack, carbonization and chloride ion penetration. The addition of PF can enhance the durability properties except for chloride ion penetration resistance. Generally, though with few exceptions, the increased dosage of CTF or PF would improve the strengthening effect on the durability of single fiber reinforced concrete. The addition of VS can either enhance or weaken the above five aspects of durability properties, and its effect varies much with the fiber dosage. (2) Hybrid fiber is found to have a positive synergistic effect and enhance the above five aspects of durability properties of concrete. The concrete reinforced with the hybrid fiber combination of 1.2 kg/m 3 CTF, 2.0 kg/m 3 PF and 2.0 kg/m 3 VS may achieve the optimal durability properties. (3) CTF, PF and VS, especially their hybrid combinations, are found to effectively prolong the service life of concrete structure in the carbonization and chloride ion corrosive environment. The research findings obtained in this paper can supplement the study on the durability of fiber reinforced concrete, and provide suggestions for suitable fiber type and dosage selection in actual engineering designs of fiber reinforced concrete.